Analysis of Teaching Writing Strategies - Wida Rianti; Vitri Angraini Hardi; Yeni Afriyeni; Ummi Rasyidah (STAI Hubbulwathan Duri, 2022)
The effective teaching strategy in writing class must be considered to get the best students’ writing. The aims of this research is to investigate the teachers’ teaching writing strategis in Writing class at English Language and Education Department of University of Pahlawan Tuanku Tambusai. This qualitative descriptive research used interviews in collecting data. This research uses a descriptive analysis which means that this study analyzes the strategy used by English teacher in teaching writing. The process of research involves emerging questions and procedures, data analysis inductively building from particulars to general themes, and the researcher making interpretations of the meaning of the data with a teacher as the subject of the research. This research used in-depth analytical techniques (in-depth analysis), which is reviewing the problem in case of cases. The result shows that the strategy used by the teacher, namely charts. Charts is a suitable strategy to use in teaching writing, because the strategy is designed as attractive as possible, simple, and effective so that students are interested in the material presented by the teacher. It can be used in teaching writing skill because Charts also provide a summary of the important points of the material in writing.